Manganese modulation of MAPK pathways: effects on upstream mitogen activated protein kinase kinases (MKKs) and mitogen activated kinase phosphatase-1 (MKP-1) in microglial cells - Crittenden, Patrick L. (2011)
Multiple studies demonstrate that manganese (Mn) exposure potentiates inflammatory mediator output from activated glia; this increased output is associated with enhanced mitogen activated protein kinase (MAPK: p38, ERK, and JNK) activity. We hypothesized that Mn activates MAPK by activating the kinases upstream of MAPK, i.e., MKK-3/6, MKK-1/2, and MKK-4 (responsible for activation of p38, ERK, and JNK, respectively), and/or by inhibiting a major phosphatase responsible for MAPK inactivation, MKP-1. Exposure of N9 microglia to Mn (250μM), LPS (100 ng/ml), or Mn+LPS increased MKK-3/6 and MKK-4 activity at 1 h; the effect of Mn+LPS on MKK-4 activation was greater than the rest. At 4 h, Mn, LPS, and Mn+LPS increased MKK-3/6 and MKK-1/2 phosphorylation, whereas MKK-4 was activated only by Mn and Mn+LPS. Besides activating MKK-4 via Ser257/Thr261 phosphorylation, Mn (4 h) prevented MKK-4’s phosphorylation on Ser80, which negatively regulates MKK-4 activity. Exposure to Mn or Mn+LPS (1 h) decreased both mRNA and protein expression of MKP-1, the negative MAPK regulator. In addition, we observed that at 4 h, but not at 1 h, a time point coinciding with increased MAPK activity, Mn+LPS markedly increased TNF-α , IL-6, and Cox-2 mRNA, suggesting a delayed effect. The fact that all three major groups of MKKs, MKK-1/2, MKK-3/6, and MKK-4 are activated by Mn suggests that Mn-induced activation of MAPK occurs via traditional mechanisms, which perhaps involve the MAPKs farthest upstream, MKKKs (MAP3Ks). In addition, for all MKKs, Mn-induced activation was persistent at least for 4 h, indicating a long-term effect.